Desa Maligi Pasaman Barat dalam Travelling Photography - Yani, Nesi Kusma (Institut Seni Indonesia Padangpanjang, 2022)
ABSTRACT Photography is a tool convey information in the form of fhoto visualization that can record reality. The interest in travelling photography his project entitled: Desa Maligi Pasaman Barat in Travelling Photography.Maligi village is new pearl in West Pasaman. Natural scenery, dominan community, activities of fishermen, sea potensial is still very good, still beautiful and the interesting thing in maligi is by porters carrying palmfruit to cross the Batang Maligi is Rendang lokan, oysters,groin, and sala gimih. In the pupuse of creating karua travelling photography, which is to have a story value that provides information,to the wider community so that people know the potensial that exists in the Maligi village area, at the time of shootong with the Maligi village the method of creating this work used the method of preparation,design,work,embodiment. And produce a work that the auther created in Vest Pasaman Maligi in travelling.